Linguistic interference in oral verbal participation - Coronado-Cárdenas, Mirtha Y. (2021)
Linguistic interference as phenomena resulting from the coexistence of languages, whose structure is divergent, alter and distort oral expression at the level of the production of sounds, the construction of sentences, the organization and use of a set of words that constitute a certain language; therefore, they hinder the oral comprehension and intervention of students in the teaching-learning process. The purpose of the present was to determine the influence of linguistic interference on students' oral verbal participation; explain regarding the linguistic and sociocultural factors influencing oral expression; likewise, evaluate the consequences of linguistic interference derived from subtractive bilingualism. The research was non-experimental, descriptive and explanatory. Data were collected using observation, survey and interview techniques, the instruments of which are observation cards, questionnaires and checklists. A population made up of 80 high school students from the "Los Libertadores" educational institution was covered, most of them bilingual (Quechua-Spanish) and from rural and marginal urban areas. The conclusion reached is the existence of little command of the standard Castilian language, little fluency in communication, diction errors, lexical poverty, among others.